V. Ruzgas on Vocational Training - Širiakovienė, Asta (Acta Paedagogica Vilnensia, 1991)
This article is dedicated to the centenary of the famous cultural and educational figure – teacher, educational methodologist, textbook author, translator, one of the pioneers of librarianship in Lithuania - Vincas Ruzgas (1890-1972). Noting that one of the firmest pillars creating a new Lithuanian school is history, and pedagogical legacy is an important precondition for the recovery of the national school, the article discusses Ruzgas’ thoughts about vocational training in the early years of primary school. It is stated that Ruzgas’ recommendation that at least 4-6 hours shall be allocated to manual work in the primary school, is not realized in the present day schools, but even with fewer hours Ruzgas’ methodical tips on how to organize these lessons are very useful. Teachers should note that the manual work training should be individualized as much as possible, it should take into account pupils’ hobbies and interests, and in every possible way avoid the formalistic, blind “slavery” to the curriculum. In order to arouse students’ interest and involvement various forms of training should be applied, one of which is an excursion.